Disease control in organic apple production - Mojca VIRŠČEK-MARN; Franci ŠTAMPAR (Acta Agriculturae Slovenica)
Organic fruit production is gaining importance with the growing public concern about healthy food and environment. Since the use of synthetic chemicals is not allowed in organic farming economical production of healthy fruits requires a high level of knowledge about diseases, pests, their natural enemies and the host. Practical experiences, recommendations and research results about disease control in organic apple production is reviewed in the article. Symptoms of less known diseases are also described.